2011
DOI: 10.1164/rccm.201003-0469oc
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Right Ventricular Structure and Function

Abstract: Higher levels of physical activity in adults were associated with greater RV mass independent of the associations with LV mass; similar results were found for RV volumes. Exercise-associated RV remodeling may have important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“… 23 27 while others have reported normal RV function. 19 , 28 In the present study, ARVC athletes had clearly dilated RV dimensions and severely reduced RV function. 19 , 29 Combined, our findings showed reduced LV and RV function in ARVC athletes compared with ARVC non-athletes.…”
Section: Discussionsupporting
confidence: 52%
“… 23 27 while others have reported normal RV function. 19 , 28 In the present study, ARVC athletes had clearly dilated RV dimensions and severely reduced RV function. 19 , 29 Combined, our findings showed reduced LV and RV function in ARVC athletes compared with ARVC non-athletes.…”
Section: Discussionsupporting
confidence: 52%
“…While the effect sizes seem small (ranging from 3.2% to 5.5%), they are comparable to those seen in the LV related to active smoking and diabetes mellitus and in the RV related to physical activity (e.g., a 7% increase in RVEDV and a 5% increase in RV mass with higher levels of physical activity), but more subtle than the associations we have shown in the RV related to obesity [54], [55], [56]. A few small studies have shown similar magnitudes of effect on RV tissue Doppler imaging [57], [58], [59].…”
Section: Discussionsupporting
confidence: 66%
“…While self-reported physical activity has previously been associated with higher LV mass and larger LV end diastolic volume (25-28), there are few studies that have comprehensively addressed the association between measured fitness and echocardiographic measures of LV structure and function in middle-aged adults (29). To our knowledge, this is the first paper to examine the association between measured cardiorespiratory fitness and echocardiographic measures of both LV structure and function in a large cohort of healthy, asymptomatic, middle-aged adults not referred for exercise testing.…”
Section: Discussionmentioning
confidence: 99%